2002
DOI: 10.1159/000049153
|View full text |Cite
|
Sign up to set email alerts
|

New Approaches to Clinical Trials in Vascular Dementia: Memantine in Small Vessel Disease

Abstract: Although criteria for the diagnosis of vascular dementia (VaD) are established, the diagnostic concept is still controversial and there is no regulatory guidance for clinical drug development. Clinical trials in VaD present a number of pitfalls and challenges and, so far, no compound has received regulatory approval for this indication. The methodological issues of clinical VaD trials are discussed using the development of memantine for this indication as an example. In a pooled analysis of two placebo-control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…As a result, the dosing may have been suboptimal, due to the development of untoward side effects that prevented dose escalation to neuroprotective levels. A more suitable approach would be to use therapeutic agents that selectively target excessive channel opening (e.g., uncompetitive inhibitors with a relatively fast off-rate, such as memantine (Orgogozo et al, 2002; Mobius and Stoffler, 2002; Lipton, 2006; Kaviragan and Schneider 2007) thereby retaining normal receptor functions (Lipton, 2007a). …”
Section: Parenchymal Failure: Why and How Does The Brain Die During Imentioning
confidence: 99%
“…As a result, the dosing may have been suboptimal, due to the development of untoward side effects that prevented dose escalation to neuroprotective levels. A more suitable approach would be to use therapeutic agents that selectively target excessive channel opening (e.g., uncompetitive inhibitors with a relatively fast off-rate, such as memantine (Orgogozo et al, 2002; Mobius and Stoffler, 2002; Lipton, 2006; Kaviragan and Schneider 2007) thereby retaining normal receptor functions (Lipton, 2007a). …”
Section: Parenchymal Failure: Why and How Does The Brain Die During Imentioning
confidence: 99%
“…In addition, placebo decline of the small-vessel group was clearly more pronounced than in the large-vessel type of VaD. 66 …”
Section: Pharmacotherapy In Vadmentioning
confidence: 89%
“…Patients with MMSE score Ͻ15 at baseline showed an ADAS-cog improvement of 3.2 points over placebo. 66 Additionally, the cognitive treatment effect for memantine was more pronounced in the small-vessel type group without cortical infarctions by CT or MRI. In addition, placebo decline of the small-vessel group was clearly more pronounced than in the large-vessel type of VaD.…”
Section: Pharmacotherapy In Vadmentioning
confidence: 95%
“…Effects of Memantine in VD were studied in two large double-blind six-month studies. A post hoc subgroup analysis found that placebo-treated SVD patients worsened by a mean of 1.9 ADAS-cog points, while largevessel VD patients remained nearly unchanged [32]. In a small open 22-month study dedicated specifically to SVD, Moretti et al [33] compared the effects of Rivastigmine vs. cardioaspirin in eight patients each.…”
Section: Evidence From Drug Trialsmentioning
confidence: 99%